The Use of Silence in Conversation among Women in Spanish: An Expression of Feminine Conversational Style? - Beatriz Méndez-Guerrero; Laura Camargo-Fernández (Languages, 2024)
Human communication is a multimodal phenomenon that involves the combined use of verbal and non-verbal signs. It is estimated that non-verbal signs, especially paralinguistic and kinesic ones, have a significant impact on message production. Silence in Spanish has been described as a plurifunctional communicative resource whose meanings vary depending on contextual, social, and cultural factors. The pragmatic and sociolinguistic nature of this phenomenon calls for examining each case considering the context, the social variables, and the relationship between participants. The aim of this study is to determine the use of silence in Spanish by young women. To achieve this, a corpus of 9 h of spontaneous conversations among six young Spanish university women (1.5 h per participant) was analyzed. The analysis has allowed identifying, first, a series of communicative functions of silence produced by the participants. A relationship between the duration of silence and its communicative function has also been established. Finally, differences in the use of silence by the participants have been found, determined by the interlocutor (male/female), which confirms that women use silence as a basic interactive strategy differently when talking with women and when they do so with men.